(untitled) (Papeles, 2015)
This article comes from an investigation which sought to develop a mapping of the discursive traces of otherness in areas of school violence through processes reading writers, in order to express a critical diagnosis based on an analysis of the texts prepared by the students of three private institutions located in three different social contexts through various scenarios proposed by the research team, taking into account related theoretist such as Teun van Dijk, Jürgen Habermas, Pierre Bourdieu and Michael Foucault, among others.